EFEKTIVITAS ANTARA MENGUNYAH BUAH DAN BERKUMUR JUS BUAH BENGKUANG (Pachyrhizus erosus) TERHADAP PENURUNAN PLAK - , TRI WAHYUNI; , Dr.drg. Dahlia Herawati, S.U., Sp.Perio(K). ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Dental plaque is a soft deposit in the form of thin layers (biofilms) that are firmly attached to the tooth surface or other hard structure surfaces in the oral cavity. The presence of pathological potential of dental plaque, thus need an effort to prevent the accumulation of plaque. There are two ways of plaque control which are mechanically and chemically. Plaque removal can be done by chewing bengkuang fruit and gargling bengkuang fruit juice. This study aims to find out the difference in effectiveness between chewing bengkuang fruit and gargling bengkuang juice (Pachyrhizus erosus) towards plaque reduction. This study was a quasi-experimental study with crossover design. The study samples were adolescents aged 16-18 years old by the number of 30 subjects. Thirty subjects were divided into two groups containing 15 subjects each group. In the first week, group I was given a treatment of chewing bengkuang fruit while group II was gargling bengkuang fruit juice. In the second week, the cross over design was performed by changing the treatments into each group. Group I was given the treatment of gargling bengkuang fruit juice while group II was chewing bengkuang fruit. The assessment of dental plaque score was suitable using PHP plaque score from Podshadley and Haley. The data obtained from the study were analyzed using Paired t-test. The result showed that there was a significant difference in plaque score reduction between two groups (p<0,05). In conclusion, chewing bengkuang fruit was more effective in reducing plaque than gargling bengkuang fruit juice.